2014
DOI: 10.2478/bvip-2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory findings associated with naturally occurring babesiosis in dromedary camels

Abstract: Clinical, haematological, and biochemical changes induced by naturally occurring babesiosis in dromedary camels were described. Of 258 dromedary camels studied, 34 camels suffered from fever, appetite loss, weakness, depression, and reluctant movement; abortion and/or infertility were also observed. Parasitological blood examinations were performed using Giemsastained blood smears. The clinically affected animals were diagnosed with babesiosis, with 13.17% overall morbidity. Camels that suffered from babesiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 15 publications
5
28
2
Order By: Relevance
“…The prevalence of camel piroplasmosis using microscopical examination in this study was higher than that reported in KSA [11], Egypt [5], and Iraq [6]. This could be attributed to the higher prevalence rate of ticks and biting flies infesting camel in the investigated area of the Sudan [2] (Hassan, and Salih 2009).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The prevalence of camel piroplasmosis using microscopical examination in this study was higher than that reported in KSA [11], Egypt [5], and Iraq [6]. This could be attributed to the higher prevalence rate of ticks and biting flies infesting camel in the investigated area of the Sudan [2] (Hassan, and Salih 2009).…”
Section: Discussioncontrasting
confidence: 56%
“…However, no pathognomonic clinical signs of piroplasmosis (e.g., haemoglobin-urea) were recorded during sampling. Swelum et al [11] reported some clinical, haematological, and biochemical changes due to natural infection of babesiosis in dromedary camels in Kingdom of Saudi Arabia (KSA). Camel is known to be tolerant to many diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other farm animals, studies on camel reproductive physiology are lacking because of the many complex genetic and environmental factors that contribute to the declined fertility in camels. In recent years, the number of studies on the camelid family, in terms of science and research, has greatly increased [3]. There are several ways to improve the productivity and reproductive performance of the Arabian camel [4][5][6][7][8], such as artificial insemination (AI).…”
Section: Introductionmentioning
confidence: 99%
“…Camel is an important multipurpose animal and since the old times, it has been used for transportation and produce milk, wool and meat in arid and semi-arid areas of the world [1]. Although camels are hardy animals and can tolerate the harsh conditions of arid regions because of their unique adaptive physiological characteristics, these animals face a wide variety of diseases [2,3]. Gastrointestinal and blood parasites are known to affect the health of camels leading to anemia, wasting and death in heavy infection [4].…”
Section: Introductionmentioning
confidence: 99%